Ingestive behavior of lambs fed relocated and inoculated whole-plant corn silage - Cardoso, Marcus Vinicius Santa Brígida; Mendonça, Rita de Cássia Almeida de; Queiroz, Amanda Caroliny Marques; Ferreira, Cláudia Márcia Serra; Santos, Rosana Ingrid Ribeiro dos; Faturi, Cristian; Domingues, Felipe Nogueira; Rêgo, Aníbal Coutinho do (Acta Scientiarum. Animal Sciences, 2021)
We aimed to determine the effect of relocation of whole-plant corn silage (WPCS) with different fermentation profiles on ingestive behavior of lambs. Twenty-four male Santa Inês lambs, were used in a completely randomized block design based on initial body weight (17.5 ± 1.8 kg) for the following treatments: CS: WPCS (not inoculated and not relocated); R-12h: WPCS relocated for 12h; IR-12h: WPCS inoculated with Lactobacillus plantarum and relocated for 12h; and R-24h: WPCS not inoculated and relocated for 24h. Ingestive behavior was observed as continuous (feeding, ruminating, and idling) and specific (urination, defecation, and water and salt access frequency) activities for 48h (3h intervals for a total of eight periods in 24h). The behavioral activities were affected only by periods (p = 0.0001). Feeding peaks was high at 8:00–11:00am (54.2%) and 5:00-8:00pm (54.9%) in compare to ruminating and idling at the same period. Rumination time was intense at night, at 63.7% (2:00–5:00am) and 69.7% (5:00–8:00am). Idling time (49.7%) was long after silage supply. The specific activities were intense during the morning periods. Supply of WPCS relocated up to 24h did not alter the ingestive behavior.